PENGARUH VIRAL MARKETING, KUALITAS PRODUK DAN ELECTRONIC WORD OF MOUTH TERHADAP MINAT BELI BITTERSWEET BY NAJLA - Nurul Anisah (2022)
Currently, the business world is becoming very tight because of the many business competitors that are growing rapidly with technology such as viral marketing. To maintain the "business economy" aspect, many entrepreneurs are looking for ways to maintain their business by promoting it on social media and they are trying to maintain the quality of existing products and consumers. This study was conducted to examine alternatives to find out viral marketing, product quality, and electronic word of mouth (E-WOM) affect buying interest. Bittersweet by Najla must understand consumer tastes and provide interesting content on social media, because the bittersweet Instagram account has 1,700,000 Instagram followers. This study uses the type data in the form of quantitative methods the population taken is Instagram followers from bittersweet by Najla Jakarta and a sample of 100 respondents where data is collected using a questionnaire (google form) which is distributed online through social networks.